(3GdChSW GdcHjQs - (3eMeO Hf eMeO Hf WQNGf Hf ChRdZ, CHh fUQ GdaGQGHqj, hjYQa HGdeYde GdKGfj,J (B339 (3g` s
(3ChdgG (B:s
(3aUhd cJGH GdHQgGf C ai UOQ GdcJGH H Gdbhd ai CUfGa GdHQGgjf s
(3BNQgG (B:s
(3Gf cGfJ GdCTjGA cdgG ai ReGf hgQ ai cQI GdYGde aGdReGf EPf gh cQI GdYGde hCTHGg gPg GdCbGhjd Je cJGH GdHQgGf s
(3Vef eLehY , JQJjHgG (B: (3GdYTQhfs
(3GdfSNI HgG MhGTs
(3GfXQ GdeNWhW Qbe (B305s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B194s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(240 / 15) s
Keywords: (3GdadSaI hGdefWbs